Childhood exposure to ionizing radiation from computed tomography imaging in Nova Scotia - Inman, Mark (Paediatr Child Health, 2015)
BACKGROUND: Examining radiation dose in the paediatric population is particularly important due to the vulnerability of paediatric patients (increased radiosensitive tissues and postexposure life-years) and risk for future radiogenic malignancy. OBJECTIVES: To evaluate trends in paediatric computed tomography (CT) use and ionizing radiation exposure using population-based data from Nova Scotia. METHODS: A retrospective, population-based cohort study of CT use in patients <20 years of age, from January 1, 2004 to December 31, 2011, was performed in Nova Scotia. CT examination data were retrieved from a provincial imaging repository. Trends in CT use were described, and both annual and cumulative effective dose exposures were calculated. RESULTS: In total, 29,452 CT events, involving up to 22,867 individuals were retrieved. Overall annual paediatric CT examination rates remained static (range 17.4 to 18.8 per 1000 per year). However, use in children <10 years of age decreased by >50% (P<0.001); this was counterbalanced by a steady increase among 15- to 19-year-olds (P<0.0001). Overall, 15.4% of scanned patients underwent ≥2 examinations, of which 58 patients (1.6%) exceeded 50 mSv of exposure. CONCLUSIONS: Despite a static rate in CT imaging among the entire cohort, children <15 years of age and, particularly, those <10 years of age displayed marked reductions in CT use. This may reflect increased awareness of campaigns emphasizing judicious CT use, revised clinical practice guidelines and increased availability of alternative modalities. A small subgroup demonstrated high-dose exposure (>50 mSv), and rates in individuals >15 years of age steadily increased, suggesting further exposure reduction efforts are necessary.